Magnitude and determinants of self-referrals among women seeking skilled birth attendance services: a cross-sectional hospital-based study in Marsabit County, Kenya - Adoyo, Joseph O.; Makunyi, Eliphas G.; Otieno, George O.; Yoos, Alison (International Journal Of Community Medicine And Public Health, 2021)
Background: Self-referral to higher-level hospitals by women seeking skilled birth attendance services reflects in part their non-adherence to established referral pathways. This choice results in an inappropriate utilization of resources within health system. The Kenya Health Sector Referral Strategy aims at optimising the utilization and access of facilities. The aim of this study was to determine the prevalence and factors associated with self-referral among women seeking skilled birth attendance services in Marsabit County between 1st and 31st Oct 2019. Methods: A cross-sectional study was adopted at the maternity department in the selected public hospitals in Marsabit County, by use of interviewer-administered questionnaires to collect information from 161 women, through systematic sampling between 1st and 31st Oct 2019. Chi-square and multiple logistic regression analysis were used to test for factors associated with self-referral at 95% confidence interval. Results: Of the 161 women interviewed, 47.2% (n=76) were self-referrals. The odds of self-referral to the higher level health facilities were more likely among women: - aged 25-29 (AOR 5.174, CI 1.015-26.365, p-value 0.048); those referred for other ANC services (AOR 4.057, CI 1.405-11.720, p-value 0.010); and those, - who visited the referral facility before for delivery (AOR 5.395, CI 1.411 – 20.628, p-value 0.014). However, self-referral were less likely among women who perceived privacy and confidentiality of services at the referral hospitals (AOR 0.370, CI 0.138-0.990, p-value 0.048). Conclusions: Almost half of women seeking skilled birth attendance were self-referrals, relates to a possible implication on an unprecedented increased workload at referral hospitals and underutilization of primary health facilities.